Práticas sociais de mercados informais de solo e regularização fundiária: benefícios privados ou coletivos? - Luciana Moreira Barbosa Ostos (2021)
The research aims to verify evidence of the existence of an informal soil market in Belo Horizonte, capital of the State of Minas Gerais, Brazil, choosing as study scope 5 (five) settlements of social interest. Belo Horizonte has a pioneering and institutionally consolidated housing policy, that allows evaluating the impacts of administrative actions and public investments on price changes and speed of sale of real estate, permanence or exit of families. The research presents a second objective of evaluating the propensity of families to accept the collection for the valorization of the land, considering: i) the characteristics of the family and the settlement; ii) to understand the motivation to charge, considering how the collection will be made (time and destination of the appeal). The research process unveils social practices of informal market oriented to permanence and to the exit of families, pointing out the richness and complexity of this theme. Finally, the research aims to contribute to improve the public debate on the justifications for the application of land recovery policies of those who attempt to monetize them, but for the benefit of the collectivity, for reasons of efficiency, equity and justice in the distribution of the burdens and benefits of urbanization.